CBS homogenization mutation strategy narrows the glycan binding profile of a GlcNAc-specific lectin AANL. (16th October 2019) - Su, Yanting; Ye, Xiangdong; Xu, Bo; Li, Yang; Yang, Qing; Yu, Wenhui; Song, Jiaqi; Guo, Chanyuan; Wang, Xueqing; Hart, Gerald W; Sun, Hui
Abstract: Glycosylation plays important roles in many cellular processes, such as signal transduction, cell cycle progression and transcriptional regulation. However, the identification and analysis of glycosylation are severely hampered by the low specificity or avidity of antiglycan antibodies and lectins. We have reported that a lectin AANL, which has high specificity for terminal GlcNAc glycans and contains six carbohydrate binding sites (CBSs), was used to enrich O-GlcNAcylated peptides. To further improve AANL binding specificity, we designed a CBS-homogenization strategy and restructured six mutant lectins, known as AANL1–AANL6. Affinity chromatography with GlcNAc and isothermal titration calorimetry analysis indicated that the two mutants (AANL3 and AANL6) all maintained GlcNAc binding activity. AANL6 and AANL3 showed higher specificity for terminal GlcNAc glycans than AANL, as shown by the hemagglutination assay, cell binding assays and glycan microarray analysis, and AANL6 exhibited the highest specificity. The binding activity of AANL6 for O-GlcNAcylated peptides was shown by surface plasmon resonance assays. By AANL6 affinity chromatography enrichment and mass spectrometry analysis, 79 high-confidence and 21 putative O-GlcNAcylated sites were identified on 85 peptides mapped onto 54 proteins. Most of these sites were new sites compared with reported data. These results indicate that the enrichment capacity of AANL6 is higher than that of wild-type AANL. In conclusion, the CBS-homogenization mutation strategy was successful, and AANL6 was identified as a powerful tool for O-GlcNAcylation enrichment. Our research suggests that the CBS-homogenization strategy is valuable for improving the specificity of lectins with multiple CBSs.